2011
DOI: 10.1542/peds.2011-1106
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Acetaminophen and Asthma Prevalence and Severity

Abstract: The epidemiologic association between acetaminophen use and asthma prevalence and severity in children and adults is well established. A variety of observations suggest that acetaminophen use has contributed to the recent increase in asthma prevalence in children: (1) the strength of the association; (2) the consistency of the association across age, geography, and culture; (3) the dose-response relationship; (4) the timing of increased acetaminophen use and the asthma epidemic; (5) the relationship between pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 30 publications
0
61
0
4
Order By: Relevance
“…Diğer tükürük bezleri ve parotis tükürük salgılanması oranları astımlı hastalarda sırasıyla % 26 ve % 36 oranında azalmıştır (9). Ayrıca astımlı çocuklar daha yon, kalp damar hastalıkları, kalp ritm bozuklukları, migren, göz tansiyonu (glokom) için kullanılan bazı ilaçlar; ameliyatlarda kullanılan anestezik maddeler, aspirin ve benzeri ağrı kesici ve antiromatizmal ilaçlar, röntgen incelemeleri esnasında kullanılan ilaçlar (19).…”
Section: Astim Hastaliğinin Oral Sağlik üZeri̇ne Etki̇leri̇ Astım Hastalunclassified
See 1 more Smart Citation
“…Diğer tükürük bezleri ve parotis tükürük salgılanması oranları astımlı hastalarda sırasıyla % 26 ve % 36 oranında azalmıştır (9). Ayrıca astımlı çocuklar daha yon, kalp damar hastalıkları, kalp ritm bozuklukları, migren, göz tansiyonu (glokom) için kullanılan bazı ilaçlar; ameliyatlarda kullanılan anestezik maddeler, aspirin ve benzeri ağrı kesici ve antiromatizmal ilaçlar, röntgen incelemeleri esnasında kullanılan ilaçlar (19).…”
Section: Astim Hastaliğinin Oral Sağlik üZeri̇ne Etki̇leri̇ Astım Hastalunclassified
“…Tylenol olarak asetaminofen olan ürünler aspirine duyarlı astım hastalığı olduğu bilinen insanlar için daha güvenli bir alternatif olarak kabul edilir. Buna rağmen bazı hastalarda asetaminofenin de astımla bağlantılı olduğu ileri sürülmüştür (19).…”
Section: Aspirin Ve Diğer Ağrı Kesicilerunclassified
“…However, the frequency of NSAID-induced postoperative bronchospasm is small even in patients with asthma [107,108]. Clinical studies in children with asthma who are receiving NSAIDs have shown no or only minimal temporary changes in respiratory function [109,110].…”
Section: Postoperative Analgesiamentioning
confidence: 99%
“…On the other side, we observe an alternative approach to causal assessment and evidence evaluation: Beasley et al [55] assert for instance that ''when the study findings are considered together with other available data, there is substantive evidence that paracetamol use in childhood may be an important risk factor for the development and/or maintenance of asthma'' (p. 1,570, emphasis added). An even stronger commitment to the hypothesis of causal association is expressed by McBride [56] who, considering all the evidence available (see Table 1), claims that evidence of causal association can by now be regarded as strong enough to warrant a change in prescription practice.…”
Section: Case Study: the Paracetamol Enigma In Asthmamentioning
confidence: 99%
“…On the other side, advocates of the causal link, especially McBride [56] and Beasley et al [55], point to the joint support of different and independent sources of evidence as a valid basis for dropping any need for RCTs. This corresponds to the idea that amalgamation of heterogeneous evidence may be a valid alternative to hypothesis testing when safety signals 7 coming from different sources are suggestive of causal association even though they cannot conclusively prove it.…”
Section: Case Study: the Paracetamol Enigma In Asthmamentioning
confidence: 99%